Patterns of snow avalanche activity during the last century in Chornohora Range (Eastern Carpathians, Ukraine): Tree-ring reconstruction coupled with synoptic conditions analysis - Decaulne, Armelle; Răchită, Ionela-Georgiana; Kholiavchuk, Dariia; Pop, Olimpiu; Holobâcǎ, Iulian Horia; Ridush, Oles; Ridush, Bogdan; Horváth, Csaba (Catena. Elsevier., 2023)
This contribution presents the first comprehensive study of snow-avalanche activity in three paths of the Chornohora range, located in southwestern Ukraine, based on historical chronicles and dendrochronology. The results are combined with a statistical analysis of meteorological drivers conducive to snow-avalanche release. While the written chronicles last from 1966 to 2015, the dendrological approach offers results back to the end of the 19th century; however, if the information covers a longer time-lapse, it loses accuracy as only the winter scale is documented through the analysis of tree-ring growing patterns. Weather data highlight the synoptic scenarios over some of the avalanche events that have been recognized as major, as the three paths were concerned: 1947–48, 1976–77, 1993–94, 1998–99, 2001–02. Three weather variables are highlighted: the formation of a consistent snow cover as early as November; positive mean daily temperature in April commands late winter avalanches if the snow cover is maintained with recurrent snowfall. Temperature warming and precipitation increase are also noted in the climatological trends in Chornohora range; however, the winter temperature remains stable, and the snow-avalanche regime might not be affected in the area in the near future.